Diagnostic evaluation as strategy for increasing proficiency in Portuguese Language (Research, Society and Development, 2020)
Considering the diagnostic evaluation as an important means to improve students' learning, this article has the general objective of presenting the case of the Colégio Estadual Liceu de Caucaia, which used the results presented by the Diagnostic Evaluation of the Secretary of Education of the State of Ceará to support actions pedagogical, aiming at increasing the level of proficiency in Portuguese Language of the students of the 3rd grade of High School of that school. Based on Luckesi (2008) and Perrenoud (1999). In this sense, we use exploratory research and bibliographic research and case study as methods, and so we conclude that this study places evaluation as an instrument that can be used in favor of learning, showing in a practical way, that it, in fact, it should be the beginning of a process to improve student learning. In addition, we specifically aim to discuss the importance of the school appropriating the results of the SEDUC Diagnostic Assessment (Ceará State Education Secretariat) in order to increase the students' interpretation and reading skills and, consequently, increase the level of proficiency in the evaluation of the Permanent Evaluation System for Basic Education in Ceará - SPAECE.